KAJIAN SOSIOLINGUISTIK KATA MOE YANG DIGUNAKAN DALAM KOMUNITAS OTAKU JEPANG - Erni Susanti; Arza Aibonotika; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed at finding out variation of word form, meaning, and function of moe word which is used by Otaku Japanese Community. This research used some theories from J.D Parera (2004), Sudjianto and Ahmad Dahidi (2007), and from Abdul Chaer and Leonie Agustina (2010). The method of this research is qualitative descriptive method. The data was collected from anime, drama and Japanese film. The result showed that moe word used only by Otaku community. Variation of moe word are moe, moeru, moeta, moenai, and moe moe. Generally, the meanings of moe word are love emotion, or like something excessively, both the animate objects or inanimate objects, and situation. Moe word has three function, they are emotive function, referential function, and phatic function.Keywords: moe, otaku, form, meaning, function